2008
DOI: 10.1080/10428190802007734
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling reveals specific gene expression signatures in gastric MALT lymphomas

Abstract: The purpose of this study is to identify genes that are involved in the etiology of Helicobacter pylori induced gastric MALT lymphoma. We compared gene expression profiles of gastric MALT lymphoma with their corresponding gastric MALT (chronic gastritis with formation of follicles and aggregates). cDNA microarrays were used to compare these two tissue types from the same patient (n = 21). Quantitative PCR and immunohistochemical staining were performed to validate the microarray results. Three hundred and fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It has both soluble and membrane forms, and is emerging as an interesting immune-modulating molecule [ 47 , 48 , 49 ]. Prior studies have shown that CD83 is a downstream target of NFkB , and can be detected on solid and hematologic malignancies, and has been shown to influence the tumor microenvironment [ 50 , 51 , 52 , 53 , 54 , 55 ]. In patients with Hodgkin lymphoma, it can be secreted from tumor cells to influence expression of PD1 in surrounding T cells [ 26 ], and there are promising results using nivolumab in Hodgkin lymphoma patients [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has both soluble and membrane forms, and is emerging as an interesting immune-modulating molecule [ 47 , 48 , 49 ]. Prior studies have shown that CD83 is a downstream target of NFkB , and can be detected on solid and hematologic malignancies, and has been shown to influence the tumor microenvironment [ 50 , 51 , 52 , 53 , 54 , 55 ]. In patients with Hodgkin lymphoma, it can be secreted from tumor cells to influence expression of PD1 in surrounding T cells [ 26 ], and there are promising results using nivolumab in Hodgkin lymphoma patients [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Series of 4 μm longitudinal sections were cut and stained with hematoxylin-eosin. Immunohistochemical stainings were conducted as previously described [ 12 ]. Following primary antibodies were used: monoclonal rat anti-mouse CD45R 1:200 (B220, clone RA3-6B2) (BD Pharmingen); polyclonal rabbit anti-cytokeratin 1:500 (catalogue number: Z0622; Dako GmbH).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that different host gene polymorphisms in genes such as IL-1 , CTLA4 and GST T1 are associated with increased inflammatory responses and consecutively with higher incidence of MALT lymphomas [ 8 11 ]. Previously, our group found that phospholipase C gamma 2 (PLCG2) is overexpressed in MALT lymphoma tissue [ 12 ]. In normal B-cells, B-cell receptor (BCR) antigen-binding results in PLCγ2 phosphorylation by Syk (spleen tyrosine kinase) and Btk (Bruton´s tyrosine kinase).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that Helicobacter pylori -specific tumor infiltrating T cells support the growth of MALT lymphoma cells [192]. A gene expression profiling study comparing non-malignant MALT tissue with MALT lymphoma tissue revealed an overexpression of CD1c, CD40, CD83, CD86, CD122 and HLA-D in the latter, suggesting the involvement of APCs and possibly T cells in this disease [193]. Infiltrating T cells are mostly Tregs and T H 2 cells [194], which are presumably attracted by tumor-secreted CCL17 and CCL22 and offer support via CD40-CD40L interaction [195].…”
Section: Immune Cells In the Tumor Microenvironmentmentioning
confidence: 99%